Hip-Hop-Based Education as Extracurricular Activity: A Case Study of Learning English Using Rap in Muhammadiyah Elementary School - Lestari, Sri (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
As one of the learning media, music has been used in hip-hop extracurricular classes at an elementary school in Indonesia. This study aimed to analyze the characteristics of learning English by using music on how teacher exposure English and culture to the students. This study used a qualitative method with purposeful sampling technique with extreme case sampling strategy. The data obtained from observation, teacher interview, and video stimulated recall. The results of teaching English with rap music in the hip-hop extracurricular classes included speed rap, rhyming word, verb rap, and battle rap lyric. These teaching activities emphasized only on the form and word meaning. Hip-hop culture was taught through language and style. Teacher taught the student to know hook while he was concerning about student’s English level. Besides, rap styles were taught on how the student dance and wear costume while they were performing in the stage. Since the school has Islamic identity, the teacher integrated the rap styles with Islamic culture. Thus, the teacher preferred to teach his own rap creation rather than adopted rap content from internet or other sources. Although there were no significant results in improving students' English comprehension, hip-hop music in extracurricular classes makes students feel happy and relaxed. Laforgue-Bullido, Abril-Hervás, & Malik-Liévano (2024) stated that the potential benefit of hip-hop as an educational tool by making subject content more engaging, which encouraged teachers to use it as hook’ to capture student’ interest.